Successful Anesthetic Management from Separation Surgery of Pygopagus Conjoined Twin; Lesson-Learning With A Teleanesthesia - Adhi, Mahendratama Purnama; Utariani, Arie; Andriyanto, Lucky (Indonesian Journal of Anesthesiology and Reanimation, 2022)
Introduction: The management of conjoined twins requires multidisciplinary teamwork. The complex problems in conjoined twin separation surgery are challenging for anesthesiologists without experience in the management of conjoined twins. Objective: To describe anesthetic management and utilization of teleanesthesia in conjoined twin separation surgery. Case Report: Sixty days-old pygopagus type conjoined twins, with a total body weight of 7030 grams. Both babies looked healthy, moved actively, found no respiratory function disorders, were hemodynamically stable and had no congenital abnormalities. The sacral region's computerized tomography scan (CT-scan) reveals conjoined twins with skin unification and subcutaneous in the perianal region and no internal-vertebral-spinal fusion. Two anesthesia teams performed the management of anesthesia. After confirming there was no cross-circulation with the atropine test, we alternately induced anesthesia by inhalation technique while maintaining spontaneous breathing. Anesthesia was maintained with sevoflurane 2.0-3.0 vol%, in a mixture of oxygen and air with a flow of 4 L/min using Jackson Reese. Circulating volume, hemodynamic stability, and normothermia were maintained intraoperatively. The separation surgery lasted 20 minutes, and the total surgical time for each baby was two hours. Awake extubation was performed immediately after the surgery was complete. Both babies underwent postoperative care at the PICU and were discharged on day 11. During the pre-operative for surgery, the local team conducted telemedicine consultations with the pediatric anesthesia team at Dr. Soetomo hospital and performed intra-anesthesia telementoring. Conclusion: Careful preparation and pre-operative evaluation, proper intra-anesthesia maintenance and monitoring, as well as good communication and teamwork, are keys to successful anesthesia management in conjoined twin separation surgery. Consultation and assistance from an experienced team during surgery using teleanesthesia are significantly beneficial to the anesthesiologist without experience in conjoined twin separation surgery.